THE PRINCIPLE OF LEGALITY IN THE DYNAMICS OF CRIMINAL LAW INTERPRETATION: A NORMATIVE STUDY ON THE LIMITS OF JUDICIAL AUTHORITY - Irwan Triadi; Dhikma Heradika (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
The principle of legality is a fundamental concept in the Indonesian criminal justice system, ensuring legal certainty and the protection of human rights from arbitrary criminal punishment. However, the rapid development of modern crimes often leads to legal gaps or vague norms that require judges to conduct judicial law-finding (rechtsvinding) when resolving criminal cases. This research aims to analyze the position of the principle of legality as a legal limit to judicial authority and examine how far judicial law-finding can be carried out without violating the essential principles of criminal law. This study employs a normative legal research method with a statute approach, conceptual approach, case approach, and historical approach. The results demonstrate that the principle of legality plays a crucial role in restricting judicial interpretation to prevent the creation of new offenses that may harm defendants and to ensure punishment can only be imposed based on pre-existing laws. Nonetheless, judicial law-finding remains necessary to address contemporary crimes that are not yet regulated under statutory law. Therefore, a proportional balance between legal certainty and substantive justice is required so that the principle of legality and judicial law-finding can work synergistically within Indonesia’s criminal justice system.